The beautiful game for women: A spotlight on the 2023 Women's football medicine conference - Andrea B. Mosler; Kerry Peek; Matthew Whalan (Elsevier, 2023)
Summary: The 9th FIFA Women's World Cup (FWWC) marked several milestones: the first hosted by two Nations, held in the Southern Hemisphere, comprising 32 teams, and >1.9million spectators (FWWC attendance record). The overwhelming success of the tournament stimulated huge public interest in women's football. The importance of maximising player health was apparent throughout the tournament with injuries and illnesses affecting team selection and performance, emphasising the need for continued focus on women's football player health. This short report summarises the key takeaway messages from the Women's Football Medicine Conference held online during the round stages of the 2023 FWWC.